2020
DOI: 10.1103/physrevd.101.063503
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-in production of dark matter prior to early matter domination

Abstract: Freeze-out or freeze-in during a period of early matter domination can yield the correct dark matter abundance for σannv f < 3 × 10 −26 cm 3 s −1 . However, in a generic non-standard thermal history, such a period is typically preceded by other phases. Here, we study nonthermal production of dark matter in a simple post-inflationary history where a radiation-dominated phase after reheating is followed by an epoch of early matter domination. Focusing on the freeze-in regime, we show that dark matter production … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…The first possibility is that n X is increased due to (nonthermal) production of X via direct φ decays to these X states. In particular, it has been observed that by adjusting the φ branching fraction to DM one can reproduce the observed relic density in a large range of scenarios [42,280,281,282,283,284,285,286,287,288,289,290,291,292].…”
Section: The Transition To Radiation Dominationmentioning
confidence: 99%
“…The first possibility is that n X is increased due to (nonthermal) production of X via direct φ decays to these X states. In particular, it has been observed that by adjusting the φ branching fraction to DM one can reproduce the observed relic density in a large range of scenarios [42,280,281,282,283,284,285,286,287,288,289,290,291,292].…”
Section: The Transition To Radiation Dominationmentioning
confidence: 99%
“…As mentioned previously, the generation of a large amount (O(10 4 ) ) of entropy in the early Universe due to the late decay of the flat direction responsible for the breaking of FSU( 5) is a generic feature of FSU(5) cosmology [13][14][15]21,22], so we do not interpret this adiabatic calculation of χ h 2 as a necessary constraint. Indeed when accounting for the late entropy production, we expect that parameters yielding h 2 ∼ 100 − 1000 would correspond better to the present relic density h 2 0.1 (see [76,77] for related work).…”
Section: Universal Boundary Conditionsmentioning
confidence: 85%
“…We finally note that the case of freeze-in depends on the initial host-sector temperature because freeze-in of Φ occurs in RD, such that the time of peak Φ production from the background occurs at the initial time (see [39] for details of freeze-in during RD before EMD). In our numerical calculations, we chose the initial time arbitrarily, with an initial energy density configuration consisting of dominant radiation and negligible Φ.…”
Section: Jhep11(2020)133mentioning
confidence: 99%
“…One can see this by analyzing the system in(5.3). For more on the effects of a large abundance of radiation during EMD, see[38,39].…”
mentioning
confidence: 99%